Curating Object-Oriented Collections Using the TEI - Brent Nelson (Journal of the Text Encoding Initiative)
This article considers the possibilities and challenges in using TEI-based XML markup for curation of objects mentioned in historical documents such as catalogues and inventories, but also in unstructured forms such as diaries and personal correspondence. It takes as a case study documents related to early modern collections of curiosities. It first considers how far the current guidelines for manuscript description can be generalized for encoding other kinds of material objects and their contexts. It then examines what more is required for treating mentions and descriptions of objects in historical documents. It argues that the core affordance of curation for such materials is the ability to identify and select what constitutes a mention of an object and to relate that mention to its immediate context, including its relationships to object groupings.